A Portrait of a Child-Friendly School in Creating a Bullying-Free Learning Environment at MI Muhammadiyah 01 Payaman - Dini Nur Kholifatun Nisa; Humairah Humairah; Ahmad Ipmawan Kharisma (STAI Auliaurrasyidin Tembilahan, 2026)
Child-Friendly Schools are educational policy programs designed to fulfill children’s rights, provide adequate facilities, support effective learning, and create safe, comfortable, and healthy learning environments. Although previous studies have examined Child-Friendly School implementation, research specifically describing its role in creating bullying-free learning environments at the elementary madrasah level remains limited. This study aims to describe the implementation of a Child-Friendly School in creating a bullying-free learning environment at MI Muhammadiyah 01 Payaman. A descriptive qualitative design was employed, involving the principal, teachers, and students as research participants. Data were collected through observations, semi-structured interviews, document analysis, and field notes. Data were analyzed using the Miles and Huberman model, while credibility was established through source, technical, and time triangulation. The findings indicate that the school has implemented the main Child-Friendly School indicators, including child-friendly policies, student-oriented curriculum implementation, trained educators and education personnel, supportive facilities and infrastructure, child participation, and parental and community participation. These indicators contributed to a safe, comfortable, inclusive, and supportive learning environment and strengthened efforts to prevent bullying. However, several aspects require further improvement, particularly the cleanliness of some facilities and limited collaboration with external community institutions. The study highlights the importance of continuous implementation, monitoring, and development of Child-Friendly School indicators to strengthen bullying prevention and support students’ holistic development.